Efecto de la fertilización npk en el rendimiento de Maíz pimte en VIRÙ, LA LIBERTAD - Mozo Aguilar, Carlos Efigenio (2014)
The present investigation entitled "Effect of NPK fertilization on maize yield in Viru pimte - Freedom" was held during the months of December 2012 to May 2013 in Fundo Santa Rosa, Viru District, Province Viru, Department of La Libertad._x000D_ The aim of this study was to determine the effect of NPK fertilization on maize yield PIMTE in Sector Santa Elena, Province of Viru, Department of La Libertad._x000D_ 3 factors were assessed fixed nitrogen dose addition; Phosphorus and potassium, were used as sources: Urea 46 % N, superphosphate Triple Calcium 46 % P2O5 and Potassium Chloride 60 % K2O. INIA irrigation system for the respective irrigation was used; other cultural practices were common to corn crop management. This work was conducted in completely randomized design (RCBD) blocks, factorial 3 x 3 with three replications. Performance, long ear, ear diameter, number of rows per ear, number of kernels per row, number of grains per ear, 100-grain weight and shelling percentage: The following parameters were evaluated._x000D_ It was concluded that the treatments 8 and 9 with 11.13 and 11.07 t / ha respectively, reached the highest yield; and T1 reached the lowest yield with 9.45 t / ha, respectively